The world encyclopedia of flags : an illustrated guide to international flags, banners, standards, and ensigns - Znamierowski, Alfred, 1940- (Lorenz Books, 2020)
Recounts the origins and development of various types of flags, and depicts over 600 national, regional, international, governmental, and ethnic flags or banners. Includes over 1,400 illustrations.